KEANEKARAGAMAN TUMBUHAN PAKU (Pteridophyta) DI KAWASAN AIR TERJUN CURUG EMBUN KELURAHAN MARGA BAKTI KECAMATAN LUBUKLINGGAU UTARA I. - Siti Mayasari; Ria Dwijayati; Nopa Nopiyanti; Linna Fitriani (Nusantara Hasana Journal, 2022)
This study aims to determine the diversity index of ferns found in determine abiotic factors and the sepecies of ferns (Pteridophyta) in the area of Curug Embun Waterfall, Marga Bakti District, North Lubuklinggau District I. The research method used is quantitative method. The data collection technique in this study used a purposive sampling technique using the roaming  method.  The  results  showed  that  the diversity  of  ferns  (Pteridophyta)  in  the Waterfall Area of Curug Embun, Marga Bakti Village, was found in 4 orders consisting of; Selaginellales, Gleichenialales, Polypodiales and Chizaeales. Consists of 11 families namely: Selaginellaceae, Gleicheniaceae, Davaliaceae, Dryoptericeae, Pteridaceae, Aspleniaceae, Blechnaceae, Onocleaeceae, Athyriceae, Polypodiaceae, Lygodiaceae. And consists of 13 genera, namely: Selaginella, Gleichenia, Davalia, Nephrolepis, Rumohra, Drynaria, Dryopteris, Adiantum, Stenochlaena, Blchnum, Athyrium, Phymatodes, Drymoglossum and Lygodium. Based on the results of measurements of abiotic factors in the Curug Embun Waterfall area, soil pH was obtained with an average of 7-8, air temperature ranged from 29-33.2ºC, soil humidity ranged from 71-83%, and light intensity was 1367.33 lux. and the results of the analysis of the diversity of H' species of the Pteridophyta division in the Curug Dew Waterfall area obtained 2.511, dominance obtained 0.076, species density obtained 0.637 and relative density obtained 100%.